‘New rights we grant not, but the old declare’ : le Henry V de Roger Boyle (1664), ou Shakespeare ‘restauré’ - Denis Lagae-Devoldère (Etudes Epistémè)
Roger Boyle’s History of Henry V (1664) is a Restoration rewriting of Shakespeare’s famous play, itself a play about the restoration of a king into his lawful rights and ancient claims. Taking into account the latest research on the theatrical and political links between Boyle’s own agenda and Charles II’s « restored » reign, this article aims at looking into some of the structural, stylistic and dramatic devices used by Boyle in this very successful play – all items more than often neglected, if not ignored, by the critics, showing restoration as a concept in its multifarious shapes and forms.